ANALISIS PENAFSIRAN QS. AL-ANKABUT [29]: 8: (STUDI KOMPARATIF METODE TAFSIR TAHLILI DAN TAFSIR) - Afni Nor Alfiqh, Izza; Dita Sari, Dewi; Azmi Kholilulloh, Ulul (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2024)
This study aims to compare the tahlili and ijmali interpretation methods of the Qur'anic verse Surah al-Ankabut verse 8. The tahlili interpretation method emphasizes in-depth analysis of each word and sentence, while the ijmali interpretation method tends to provide a more general interpretation. The analysis of this interpretation approach is done by detailing the meaning and context of QS. al-Ankabut[29]: 8 using the tahlili interpretation method, then comparing it with the ijmali interpretation method to get a broader perspective. The results show that the tahlili interpretation method can reveal the deeper nuances of the meaning of the verse, while the ijmali interpretation method provides a broader and more general picture. This finding contributes to the development of understanding of interpretive methods, as well as providing new insights related to the interpretation of QS. al-Ankabut[29]: 8 from the perspective of tahlili and ijmali interpretations. This study is expected to provide benefits in the context of developing the science of interpretation of the Qur'an and supporting a better understanding of the verses of the Qur'an holistically.